Diameter-independent skyrmion Hall angle observed in chiral magnetic multilayers - Katharina Zeissler; Simone Finizio; Craig Barton; Alexandra J. Huxtable; Jamie Massey; Jörg Raabe; Alexandr V. Sadovnikov; Sergey A. Nikitov; Richard Brearton; Thorsten Hesjedal; Gerrit van der Laan; Mark C. Rosamond; et al. (Nature Communications, 2020)
Magnetic skyrmions are promising objects for future spintronic devices. However, a better understanding of their dynamics is required. Here, the authors show that in contrast to predictions the skyrmion Hall angle is independent of their diameter and motion is dominated by disorder and skyrmion-skyrmion interactions in the system.